Export of glutathione by some widely used Salmonella typhimurium and Escherichia coli strains. - Owens, R A (1986)
Significant levels of extracellular glutathione (GSH) were detected in aerobically grown cultures of some strains of Salmonella typhimurium LT-2 and in Escherichia coli K-12, B, and B/r but not in cultures of nine freshly isolated clinical isolates of E. coli. Cultures of S. typhimurium generally contained less total GSH (intracellular plus external) than did E. coli cultures. S. typhimurium TA1534 contained about 2 mM intracellular GSH and exported about 30% of its total GSH. The external GSH concentration increased logarithmically during exponential growth and peaked at about 24 microM in early-stationary-phase cultures. External accumulation of GSH was inhibited by 30 mM NaN3. GSH was predominantly exported in the reduced form. Two-dimensional paper chromatography of supernatants from cultures labeled with Na2(35)SO4 confirmed the presence of GSH and revealed five other sulfur-containing compounds in the media of S. typhimurium and E. coli cultures. The five unidentified compounds were not derivatives of GSH.